Menakar Perbedaan Kebijakan Pendidikan Studi Komparatif Antara Indonesia dan Finlandia - Miftahul Husnah; Mislaini Mislaini; Intan Lestari (Moral : Jurnal kajian Pendidikan Islam, 2024)
In its implementation, previously designed educational programs often do not run as planned. This encourages the emergence of new policies to overcome the problems that arise, with the aim of realizing equitable and quality education as mandated by law. As a developing country, Indonesia is considered to need to study and adopt an education system that has been proven successful in other countries. One of the countries that can be used as an example in this case is Finland. This study uses a meta-analysis method. The results of the study show that there are a number of aspects of education policy in Finland that can be applied in Indonesia. It is hoped that by improving the quality of education, Indonesia will be able to produce a generation that is competent and able to compete at the global level.